2022
DOI: 10.1007/s10237-021-01553-2
|View full text |Cite
|
Sign up to set email alerts
|

Image-based radiodensity profilometry measures early remodeling at the bone-callus interface in sheep

Abstract: Bone healing has been traditionally described as a four-phase process: inflammatory response, soft callus formation, hard callus development, and remodeling. The remodeling phase has been largely neglected in most numerical mechanoregulation models of fracture repair in favor of capturing early healing using a pre-defined callus domain. However, in vivo evidence suggests that remodeling occurs concurrently with repair and causes changes in cortical bone adjacent to callus that are typically neglected in numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…4,5 Although it is commonly noted that remodeling is the final stage of bone healing, it has been shown that remodeling occurs in tandem with callus formation in the earliest stages of fracture repair. 10,11 To study this complex process, researchers choose model systems and experimental methods based on the desired mechanistic or outcome-oriented insights needed to test their hypotheses. Some experiments seek to mimic as many aspects of human fractures as possible, while others use highly standardized surgeries and genetically inbred animal models.…”
Section: The Fracture Healing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although it is commonly noted that remodeling is the final stage of bone healing, it has been shown that remodeling occurs in tandem with callus formation in the earliest stages of fracture repair. 10,11 To study this complex process, researchers choose model systems and experimental methods based on the desired mechanistic or outcome-oriented insights needed to test their hypotheses. Some experiments seek to mimic as many aspects of human fractures as possible, while others use highly standardized surgeries and genetically inbred animal models.…”
Section: The Fracture Healing Processmentioning
confidence: 99%
“…Finally, bone remodeling commences, which consists of an intricate balance between resorption of the cartilage callus and primary bone in coupled remodeling 4,5 . Although it is commonly noted that remodeling is the final stage of bone healing, it has been shown that remodeling occurs in tandem with callus formation in the earliest stages of fracture repair 10,11 …”
Section: Introductionmentioning
confidence: 99%